Dynamics of changes in the mental sphere of man - Polak-Szabela, Anna; Porzych, Katarzyna; Porzych, Martyna; Hadzik, Kajetan; Kędziora-Kornatowska, Kornelia (Medical and Biological Sciences, 2015)
Life-span psychology assumes that development is multidimensional and multidirectional process that lasts throughout life, from birth until death. The cycle of this process includes both progression and regressive changes. Changes in cognitive functioning appearing in the elderly are the result of transformations occurring in the nervous system. This leads to a reduction in psychomotor skills, memory processes, learning as well as changes in thinking, emotions and motivation. Older people, however, do not lose the ability to participate in the intellectual life. The decrease in efficiency does not occur simultaneously in all directions nor equally. Due to the body's compensatory abilities, new intellectual capabilities may occur in older people. Mental training, especially cultivated throughout life, including old age, is of great importance for maintaining cognitive performance in the elderly.